(untitled) (Journal of Asian Development Studies, 2024)
English language has been recognized as the lingua-frankand had wider scope throughout the globe. Degrees with specialization in English have higher scope in the job market and bureaucracy as well. Sustainable development Goals (SDGs)are the most important conceptsfor sustainable development thatmust be considered in our curriculum to increase awareness among learnersto promotesustainability.This study is vital because of it investigates potential contributions of undergraduate English courses to sustainable development.In order to improve the world the sustainable development goals (SDGs) aim to solve problems with justice, quality education, gender equality and climate change. Through this lens of analysis, the study aims to demonstrate how the literature, critical thinking and language skills taught in courses can raise students’awareness of global issues, promote conservative behavior, and motivate them to make a constructive contribution to society. The scope of the study is that it is novel in nature and focuses the curriculum development. Ithelps to create a strongand stable society. The study used qualitative approach and collectsthe data from the contentof English curriculum courses that based on contentrelated to SDGs concept to increase awareness in learners to promote sustainability. The study aims to analyze the content related to the Sustainable Development Goals SDGs concept to increase awareness in learners to promote sustainable development in the current curriculum of the English in undergraduate Program in universities at Karachi Sindh Pakistan. The total 8 courses of the Englishcurriculum arethe sample of this research,and the themes are generatedfrom this content that relatedto the SDGs concept such as environmental aspects, human rights and dignity, global issues and citizenship and educationand empowerment. The findings indicates that the English curriculum courses at undergraduate level includes content and has a courserelated to the concept of SDGs that increases awareness in students about sustainable development